Chemical Constituents of Micromelum Minutum and Acronychia Laurifolia (Rutaceae) - Yap, Yun Hin @ Md. Taufiq (1994)
A chemotaxonomic investigationon the leaves and stems of Micromelum minutum (Rutaceae), has resulted in the isolation of six components. The structure of these compounds was elucidated by means of spectroscopic methods including by the extensive used of various NMR techniques and al so comparison with previous studies. The use of High Field NMR is essential in structural determination of these complex molecules. With the aids of various NMR experimental techniques and other spectroscopic methods such as MS, UV and JR, the correct structures of the pure isolated compounds were established. M.minutum collected from Kelantan yielded two novel coumarins, microminutinin and 6-methoxymicromi nutinin, and a known coumann, scopoletin. From another separate collection of the plant from Pahang, a novel compound, MM5, squalene, and two known coumarin, micromelin and scopoletin have al so been isolated. A similar study on the leaves and stems of Acronychia laurifolia collected from Pulau Singa Besar, Langkawi Island afforded three compounds, sitosterol, seselin and an unidentified compound.